Ideologi Politik dan Motivasi Pelayanan Publik di Kalangan PNS Kota Padang - Syamsir, Syamsir -; Embi, Muhamad Ali - (TINGKAP, 2013)
Political ideology has been assumed to be correlated with public service motivation (PSM) as indicated by some researchers in developed countries. This study was designed to investigate the correlation between political ideology and PSM among civil servants in Padang City. Mixing approach was used in this study. Using Anova test on responses by 417 respondents of civil servants in Padang City, this study tested the correlation between political ideology and PSM among the employees, in terms of the differences in the level of PSM based on political ideology followed by respondents. The findings of this study indicated that political ideology was significantly correlated to the level of PSM. Kata Kunci: Motivasi Pelayanan Publik, ideologi politik, Pegawai Negeri Sipil (PNS)